MARCOMM'S PERSUASIVE COMMUNICATION STRATEGY IN SHARIA-BASED PRINT ADVERTISING DESIGN - Bintang Hendra Fibiantoro; Gibbran Prathisara (Program Pascasarjana UIN Sumatera Utara, 2025)
The rapid development of the advertising industry in the digital era has created increasingly intense competition among businesses in communicating their products to target audiences. This study aims to analyze the persuasive communication strategies implemented by Syafaat Marcomm in designing sharia-based print advertising, while also exploring how Islamic values are integrated into modern marketing practices. Employing a qualitative descriptive approach, data were collected through observation, interviews, documentation, and literature study, then analyzed using the interactive model of Miles and Huberman through the stages of data reduction, data display, and conclusion drawing. The findings reveal that conventional branding generally emphasizes profit and image enhancement, whereas sharia-based branding focuses on ethical and spiritual principles such as honesty, trust, justice, and truthful communication. Syafaat Marcomm applies a three-level integrated branding strategy, namely conducting research and brand audits, designing persuasive messages across print and digital media with ethical language and visual symbols, and building long-term consumer loyalty through value-based communication. Despite challenges such as limited budgets and public skepticism toward sharia branding, the study concludes that persuasive communication rooted in sharia principles is both effective and relevant for strengthening consumer trust, brand awareness, and business sustainability in Indonesia's competitive advertising landscape.